Natural gas container transportation: the alternative way to solve the world’s energy transportation problems - Shendrik, A. M.; Fyk, M. I. (Academic Publishing House Researcher, 2014)
The container gas transportation for low and medium level consumers as an alternative to pipelines is considered. The options for gas supply schemes, based on road and rail transport are given. The advantages and disadvantages of both types of gas transporting are described, the areas of their effective using are separated in the article. Promising implementations of technology in environment of economic crisis and also considering world trends of energy development are presented. The most advanced organization of compressed gas condensate transportation of unprepared gas fields in large diameter universal cylindrical balloons (up to 1000 mm) are reasoned. The problem of compressed gas sea transportation are well disclosed, but the alternative ways of gas transportation by land are not investigated enough. Compressed Natural Gas (CNG) Technology - is new promising technology for natural gas transportation by specially designed vessels – CNG-vessels. The feature of this technology is that natural gas can be downloaded directly near gas deposits and unloaded - directly into the customer's network. This eliminates significant capital investments in underwater pipelining or gas liquefaction plants. The main objects of investment are CNG-vessels themselves. The most attractive places for implementation of CNG-technology are sea (offshore) natural gas deposits. Numerous international experts estimate the natural gas transportation by CNG-vessels in 1.5-2.0 times more cost-beneficial in comparison with offshore pipelines transportation, or in comparison with LNG (Liquefied Natural Gas) shipping with natural gas transportation volume between 0.5 and 4.0 billion cubic meters per year on the route from 250 to 2,500 sea miles. This technology makes possible to provide gas supplement to the mountain and abounding in water areas, remote and weakly gasified regions. Described technology deserves special attention in the case of depleted and low-power oil and gas deposits development.
Keywords: gas production industry; compressed natural gas; technology; construction; pipeline; rail transport